Plant-growth regulators alter phytochemical constituents and pharmaceutical quality in sweet potato (Ipomoea batatas L.) - Ghasemzadeh, Ali; Talei, Daryush; Jaafar, Hawa Z. E.; Juraimi, Abdul Shukor; Tengku Muda Mohamed, Mahmud; Puteh, Adam; Abd Halim, Mohd Ridzwan (BioMed Central, 2016)
Background: Sweet potato (Ipomoea batatas L.) is one of the most important consumed crops in many parts of the world because of its economic importance and content of health-promoting phytochemicals. Methods: With the sweet potato (Ipomoea batatas L.) as our model, we investigated the exogenous effects of three plant-growth regulators methyl jasmonate (MeJA), salicylic acid (SA), and abscisic acid (ABA) on major phytochemicals in relation to phenylalanine ammonia lyase (PAL) activity. Specifically, we investigated the total phenolic content (TPC), total flavonoid content (TFC), total anthocyanin content (TAC), and total β-carotene content (TCC). Individual phenolic and flavonoid compounds were identified using ultra-high performance liquid chromatography (UHPLC). Antioxidant activities of treated plants were evaluated using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay and a β-carotene bleaching assay. Anticancer activity of extracts was evaluated against breast cancer cell lines (MCF-7 and MDA-MB-231) using MTT assay. Results TPC, TFC, TAC, and TCC and antioxidant activities were substantially increased in MeJA-, SA-, and ABA-treated plants. Among the secondary metabolites identified in this study, MeJA application significantly induced production of quercetin, kaempferol, myricetin, gallic acid, chlorogenic acid, 3,5-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid. Luteolin synthesis was significantly induced by SA application. Compared with control plants, MeJA-treated sweet potato exhibited the highest PAL activity, followed by SA and ABA treatment. The high DPPH activity was observed in MeJA followed by SA and ABA, with half-maximal inhibitory concentration (IC50) values of 2.40, 3.0, and 3.40 mg/mL compared with α-tocopherol (1.1 mg/mL). Additionally, MeJA-treated sweet potato showed the highest β-carotene bleaching activity, with an IC50 value of 2.90 mg/mL, followed by SA (3.30 mg/mL), ABA (3.70 mg/mL), and control plants (4.5 mg/mL). Extracts of sweet potato